PENGARUH CORPORATE SOCIAL RESPONSIBILITY, CAPITAL INTENSITY, TRANSFER PRICING TERHADAP TAX AVOIDANCE - Icha maya anggraeni; Adi Sofyana Latif (Publika Citra Media, 2026)
This study aims to empirically determine and test the influence of Corporate Social Responsibility, Capital Intensity, Transfer Pricing on Tax Avoidance. This type of research uses a quantitative approach with secondary data taken from the company's annual financial statements for the period 2019 - 2023. The population in this study are Consumer Non-Cyclicals sector companies listed on the Indonesia Stock Exchange in 2019 - 2023 with a total population of 90 companies. The sampling technique used is purposive sampling and obtained a sample of 11 companies. The data analysis technique uses panel data regression using E-views version 12. The results of the simultaneous test show that Corporate Social Responsibility, Capital Intensity, Transfer Pricing on Tax Avoidance have a simultaneous effect. The results of the partial test show that Corporate Social Responsibility does not affect Tax Avoidance. Capital Intensity affects Tax Avoidance, Transfer Pricing does not affect Tax Avoidance.